Intercultural Competencies: Understanding High- vs. Low-Context Cultures - Pablo Lamino; John Diaz (EDIS)
This first publication in the Intercultural Competencies series provides valuable insights and recommendations on engaging diverse clientele by understanding and applying high-context and low-context cultural communication styles. Written by Pablo Lamino and John Diaz, and published by the UF/IFAS Department of Agricultural Education and Communication, November 2024.